Acellular Gellan-gum based bilayered structures for the regeneration of osteochondral defects: a preclinical study - Pereira, D. R. (2015)
In orthopaedics, the management and treatment of osteochondral (OC) defects remains an ongoing clinical challenge. Autologous osteochondral mosaicplasty has been used as a valid option for OC treatments although donor site morbidity remains a source of concern [1]. Engineering a whole structure capable of mimicking different tissues (cartilage and subchondral bone) in an integrated manner could be a possible approach to regenerate OC defects. In our group we have been proposing the use of bilayered structures to regenerate osteochondral defects [2,3]. The present study aims to investigate the pre-clinical performance of bilayered hydrogels and spongy-like hydrogels in in vivo  models (mice and rabbit, respectively), in both subcutaneous and orthotopic models. The bilayered structures were produced from Low Acyl Gellan Gum (LAGG) from Sigma-Aldrich, USA. Cartilage-like layers were obtained from a 2wt% LAGG solution. The bone-like layers were made of 2wt% LAGG with incorporation of hydroxyapatite at 20% and 30% (w/v). Hydrogels and spongy-like were subcutaneouly implanted in mice to evaluate the inflammatory response. Then, OC defects were induced in rabbit knee to create a critical size defect (4 mm diameter and 5 mm depth), and then hydrogels and sponges implanted. Both structures followed different processing methods. The hydrogels were injected allowing in situ  crosslinking. Unlike, the spongy-like were pre-formed by freeze-drying. The studies concerning subcutaneous implantation and critical size OC defect were performed for 2 and 4 weeks time, respectively. Cellular behavior and inflammatory responses were assessed by means of histology staining and biochemical function and matrix deposition by immunohistochemistry. Additionally, both OC structures stability and new cartilage and bone formation were evaluated by using vivo- computed tomography (Scanco 80). The results showed no acute inflammatory response for both approaches. New tissue formation and integration in the adjacent tissues were also observed, which present different characteristic behaviors when comparing hydrogels and sponges response. As future insights, a novel strategy for regeneration of OC defects can be designed encompassing both, hydrogels and spongy-like structures and cellular approaches. References: 1. Espregueira-Mendes J. et al. Osteochondral transplantation using autografts from the upper tibio-fibular joint for the treatment of knee cartilage lesions. Knee Surgery, Sports Traumatology, Arthroscopy 20,1136, 2012. 2. Oliveira JM. et al, Novel hydroxyapatite/chitosan bilayered scaffold for osteochondral tissue-engineering applications: Scaffold design and its performance when seeded with goat bone marrow stromal cells. Biomaterials 27, 6123, 2006. 3. Pereira D R. et al. Gellan Gum-Based Hydrogel Bilayered Scaffolds for Osteochondral Tissue Engineering. Key Engineering Materials 587, 255, 2013.